Prevalence of chlamydia and mycoplasm genital infections in women aged ≥ 20 years and < 20 years: a comparison between 2008 and 2010 (Italian Journal of Public Health, 2010)
Background: Sexually transmitted infections represent a serious problem of public health. Chlamydia andMycoplasms infections are involved in the pathogenesis of female infertility and in other serious gynaecologicand obstetric or neonatal complications. This study aims to analyze the prevalence of these infections in adultwomen and teenagers and to evaluate variations between 2010 and 2008.Methods: Women of reproductive age, sexually active, regardless of symptoms, examined only once forChlamydia or, alternatively, for Mycoplasms vaginal/cervical infections, in 2008 (January-May) and in 2010(January-May), at the Sandro Pertini Hospital were considered. Chlamydia was detected using Polimerasechain reaction; Mycoplasms were detected through culture. Patients were divided into women aged
Keywords: chlamydia; mycoplasms; genital infections; sexually transmitted infections; adolescents